PENGARUH JENIS PUPUK ORGANIK DAN VARIETAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annum L.) - Erita Hayati Hayati; T. Mahmud T. Mahmud; Riza Fazil (Jurnal Floratek, 2012)
This study was aimed at determining effects of organic fertilizer types and varieties on growth and yield of pepper and interaction between both factors. The research was conducted at Experiment Station of Agriculture Faculty, Syiah Kuala University, Darussalam Banda Aceh, from June to October 2010. The experiment used a randomized complete block design (RCBD), 3 x 2 with three replications. Factors studied were types of organic fertilizer, consisting of compost and cow manure and varieties, consisting of TM-999 and local varieties. Variables observed were plant height at ages of 15, 30 and 45 days after planting (DAP), number of productive branches, number of fruits per plant, fruit weight per plant, yield per plot and production per ha. Results showed that there was no significant interaction between organic fertilizer types and varieties on all observed variables. Organic fertilizers did not significantly affect plant height at ages of 15, 30 and 45 DAP, productive branches at age of 75 DAP, number of fruits per plant, fruit weight per plant, yield per plot, and yield per ha.  Varieties significantly affected plant height at age of 30 DAP, number of fruits per plant, but did not significantly affected plant height at ages 15 and 45 DAP, number of productive branches at age of 75 DAP, fruit weight per plant, yield per plot, and yield per ha.